Pengaruh Iklim Organisasi Terhadap Kinerja Karyawan Bagian Pemasaran PT Telkom Divisi Telkom Flexi Medan - dewi murniaty; yeni absah (Jurnal Media Informasi Manajemen, 2013)
The problem of study was how organizational climate influence performance of marketing employees on PT Telkom Division Telkom Flexi Medan.  The objective of the study was to find out the influence of organization climate on the marketing employee’s performance on the PT Telkom Division Telkom Flexi Medan.  Hypothesis in the study was that organizational climate influenced the marketing employee’s performance on PT Telkom Division Telkom Flexi Medan.  The data used were the primary and secondary ones.  The primary data were collected through disseminate questionnaires.  The secondary data were collected through documentation study of official document issued by marketing of PT Telkom Division Telkom Flexi Medan.  The method of analysis using linear regression tests.  The result of study from using linear regression test indicated that organizational climate influenced the marketing employee’s performance of 26,7%  and 73,3% explained by other factors not included in this research.   Keywords:  Climate of Organization, Employee’s Performance.